Synthesis, molecular modelling and anticancer evaluation of new pyrrolo[1,2-b]pyridazine and pyrrolo[2,1-a]phthalazine derivatives - Lacramioara Popovici; Roxana-Maria Amarandi; Ionel I. Mangalagiu; Violeta Mangalagiu; Ramona Danac (Taylor & Francis Group, 2019)
Two new series of heterocyclic derivatives with potential anticancer activity, in which a pyrrolo[1,2-b]pyridazine or a pyrrolo[2,1-a]phthalazine moiety was introduced in place of the 3'-hydroxy-4'-methoxyphenyl ring of phenstatin have been synthesised and their structure-activity relationship (SAR) was studied. Fourteen of the new compounds were evaluated for their in vitro cytotoxic activity by National Cancer Institute (NCI) against 60 human tumour cell lines panel. The best five compounds in terms of in vitro growth inhibition were screened in the second stage five dose-response studies, three of them showing a very good antiproliferative activity with GI50<100 nM on several cell lines including colon, ovarian, renal, prostate, brain and breast cancer, melanoma and leukemia. Docking experiments on the biologically active compounds showed a good compatibility with the colchicine binding site of tubulin.